Variation in Eoanthidium judaeense (Mavromoustakis, 1945) and E. clypeare (Morawitz, 1874) (Apoidea: Megachilidae: Anthidiini) in the Middle East: semispecies or cases of geographic dimorphism?. Issue 2 (2nd April 2020) - Kasparek, Max
Abstract : The two bee species Eoanthidium judaeense s.l. and E. clypeare s.l. are endemic to the Middle East and south-east Europe, and each of them occurs in a light form, with rich yellow and light brown maculation, and a dark form. It was found that in both taxa the light forms are restricted to the Levant and the northern belt of the Syrian desert, while the dark forms are much more widely distributed. While the transition from the dark to the light form is abrupt in E. judaeense s.l., there is a zone with intermediate forms in E. clypeare s.l. A Discriminant Function Analysis carried out on morphometric para- meters enabled 87.5% of all females and 93.9% of all males in E. judaeense s.l. to be attributed to either the light or the dark form solely on the basis of morphometric data. For E. clypeare s.l., the respective values were 79.3% (females) and 82.5% (males) when intermediate forms were not taken into account. As the colour variation is thus correlated with morphological variation and the distribution is discrete without follow- ing a geographical cline, these forms should be recognised as distinct semispecies: The species pair E. judaeense (Mavromoustakis, 1945) and E. pasteelsi (Warncke, 1980) stat. n., and the pair E. clypeare (Morawitz, 1874) and E. hoplostomum (Mavro- moustakis, 1945) stat. resurr. The areas where the dark and the light species meet are apparently secondary contact zones, and the putative hybridisation and lower level of morphometric distinctiveness found between E. clypeare and E. hoplostomum indicate that speciation is less advanced than in E. pasteelsi/E. judaeense . The dark forms seem to have evolved independently, probably as an adaptation to solar radiation and the two superspecies thus present notable examples of evolutionary convergence.